Molecular docking of Glycine max and Medicago truncatula ureases with urea; bioinformatics approaches - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER, 2016)
Urease (EC 3.5.1.5) is a nickel-dependent metalloenzyme catalyzing the hydrolysis of urea into ammonia and carbon dioxide. It is present in many bacteria, fungi, yeasts and plants. Most species, with few exceptions, use nickel metalloenzyme urease to hydrolyze urea, which is one of the commonly used nitrogen fertilizer in plant growth thus its enzymatic hydrolysis possesses vital importance in agricultural practices. Considering the essentiality and importance of urea and urease activity in most plants, this study aimed to comparatively investigate the ureases of two important legume species such as Glycine max (soybean) and Medicago truncatula (barrel medic) from Fabaceae family. With additional plant species, primary and secondary structures of 37 plant ureases were comparatively analyzed using various bioinformatics tools. A structure based phylogeny was constructed using predicted 3D models of G. max and M. truncatula, whose crystallographic structures are not available, along with three additional solved urease structures from Canavalia ensiformis (PDB: 4GY7), Bacillus pasteurii (PDB: 4UBP) and Klebsiella aerogenes (PDB: 1FWJ). In addition, urease structures of these species were docked with urea to analyze the binding affinities, interacting amino acids and atom distances in urease-urea complexes. Furthermore, mutableamino acids which could potentially affect the protein active site, stability and flexibility as well as overall protein stability were analyzed in urease structures of G. max and M. truncatula. Plant ureases demonstrated similar physicochemical properties with 833-878 amino acid residues and 89.39-90.91 kDa molecular weight with mainly acidic (5.15-6.10 pI) nature. Four protein domain structures such as urease gamma, urease beta, urease alpha and amidohydro 1 characterized the plant ureases. Secondary structure of plant ureases also demonstrated conserved protein architecture, with predominantly a-helix and random coil structures. In structure-based phylogeny, plant ureases from G. max, M. truncatula and C. ensiformis were clearly diverged from bacterial ureases of B. pasteurii and K. aerogenes. Glu, Thr, His and Gly were commonly found as interacting residues in most urease-urea docking complexes while Glu was available in all docked structures. Besides, Ala and Arg residues, which are reported in active-site architecture of plant and bacterial ureases were present in G. max urea-urease complex but not present in others. Moreover, Arg435 and Arg437 in M. truncatula and G. max, respectively were identified as highly mutable hotspot residues residing in amidohydro 1 domain of enzyme. In addition, a number of stabilizing residues were predicted upon mutation of these hotspot residues however Cys and Thr made strong implications since they were also found in codon-aligned sequences as substitutions of hotspot residues. Comparative analyses of primary sequence and secondary structure in 37 different plants demonstrated quite conserved natures of ureases in plant kingdom. Structure-based phylogeny indicated the presence of a possible prokaryote-eukaryote split and implicated the subjection of bacterial ureases to heavy selection in prokaryotic evolution compared to plants. Urea-urease docking complexes suggested that different species could share common interacting residues as well as may have some other uncommon residues at species-dependent way. In silico mutation analyses identified mutable amino acids, which were predicted to reside in catalytic site of enzyme therefore mutagenesis at these sites seemed to have adverse effects on enzyme efficiency or function. This study findings will become valuable preliminary resource for future studies to further understand the primary, secondary and tertiary structures of urease sequences in plants as well as it will provide insights about various binding features of urea-urease complexes.
Keywords: 3D structure; Metalloenzyme; Mutation; Docking; RMSD; NITROGEN-METABOLISM; CRYSTAL-STRUCTURE; WEB SERVER; LEAF; PURIFICATION; ENZYME; IDENTIFICATION; PREDICTION; PROTEINS; PATTERNS